Pendampingan Penyusunan Peta Kerentanan Berbasis WebGIS sebagai Upaya Peningkatan Mitigasi Bencana di Kawasan Pembangunan Pelabuhan Tanjung Carat, Banyuasin II, Sumatera Selatan - Herda Sabriyah Dara Kospa; Hala Haidir; Al Shida Natul; Sumi Amariena Hamim (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Tanjung Carat International Port development can potentially cause environmental and social impacts. Mitigation efforts are required by mapping the affected area’s physical and environmental indicators. The unavailability of detailed maps containing information on vulnerable areas causes difficulties in identifying the location of sensitive coastal ecosystems and strategic lands utilized by the surrounding community. Therefore, this program aims to provide a WebGIS-based vulnerability map to help the local government identify at-risk areas. The methods used included initial coordination, ground checking, GIS software data processing, and data integration through WebGIS. The output of this program was physical and environmental vulnerability maps that help policymakers to formulate mitigation decisions. This product also included a dashboard and explanatory documents to use the map practically. The existence of a vulnerability map helps improve the local government’s preparedness for the potential impacts of port development while encouraging more sustainable regional planning.